Larvicidal properties of extracts from different parts of neem (Azadirachta Indica) against Aedes Aegypti mosquitoes' larvae - Jessinta, Sandanasamy (2012)
Dengue is one of the major health problem in many countries. Aedes aegypti mosquito is the major vector of dengue fever disease. Search for larvicidal active compound(s) is one of the several attempts to find effective and affordable ways to control this mosquito. The aim of this study is to investigate the toxic effect of different solvent (acetone, chloroform, cold and hot ethanol) extracts from different parts (bark, leaf, root and seed) of Neem (Azadirachta indica) against Aedes aegypti larvae. For the larvicidal bioassay, four concentrations (50, 100, 500 and 1000 ppm) of plant crude extracts were prepared; 1 mL of DMSO was used to solubilize the extract in water. 10 larvae (second and third instar) were inserted in each solution. 2.0 % Dimethyl sulfoxide (DMSO) and untreated sets of larvae in (tap) water were also run for comparison. Data were evaluated through regression analysis. From the regression line; the LC 50 and LC 90 values were read. The larvicidal activities of the crude extracts were varied and the LC 50 and LC 90 values ranging from 50-837.5 ppm and 94-950 ppm respectively. Assays showed that leaf acetone extracts were more toxic against larvae and causes 100 % mortality at concentration of 100 ppm, while root, seed and bark extracts achieve 100 % mortality at 1000 ppm. Bioactive groups such as alkaloids and sesquiterpene lactones were screened by Thin Layer Chromatography (TLC); and the results obtained were negative for alkaloids and positive for sesquiterpene lactones. Result obtained in this study shows the potential of the crude extracts of Neem (Azadirachta indica) against Aedes aegypti larvae and this may warrant further research to determine bioactive compound(s)